Investigating the Impact of Cerium Oxide Nanoparticles Upon the Ecologically Significant Marine Cyanobacterium Prochlorococcus - Dedman, Craig J.; Rizk, Marwa M. I.; Christie-Oleza, Joseph A.; Davies, Gemma-Louise (Frontiers in Marine Science, 2021)
Cerium oxide nanoparticles (nCeO2) are used at an ever-increasing rate, however, their impact within the aquatic environment remains uncertain. Here, we expose the ecologically significant marine cyanobacterium Prochlorococcus sp. MED4 to nCeO2 at a wide range of concentrations (1 µg L-1 -100 mg L-1) under simulated natural and nutrient rich growth conditions. Flow cytometric analysis of cyanobacterial populations displays the potential of nCeO2 (100 µg L-1) to significantly reduce Prochlorococcus cell density in the short-term (72 h) by up to 68.8% under environmentally relevant conditions. However, following longer exposure (240 h) cyanobacterial populations are observed to recover under simulated natural conditions. In contrast, cell-dense cultures grown under optimal conditions appear more sensitive to exposure during extended incubation, likely as a result of increased rate of encounter between cyanobacteria and nanoparticles at high cell densities. Exposure to supra-environmental nCeO2 concentrations (i.e., 100 mg L-1) resulted in significant declines in cell density up to 95.7% and 82.7% in natural oligotrophic seawater and nutrient enriched media, respectively. Observed cell decline is associated with extensive aggregation behaviour of nCeO2 upon entry into natural seawater, as observed by dynamic light scattering, and hetero-aggregation with cyanobacteria, confirmed by fluorescent microscopy. Hence, the reduction of planktonic cells comes as a result of physical removal due to co-aggregation and co-sedimentation with nCeO2 rather than by a toxicological and cell death effect. The observed recovery of the cyanobacterial population under simulated natural conditions, and likely reduction in nCeO2 bioavailability as nanoparticles aggregate and undergo sedimentation in saline media, means that the likely environmental risk of nCeO2 in the marine environment appears low.